Sustainability synergies and trade-offs considering circularity and land availability for bioplastics production in Brazil - Guilherme Pessoa Nogueira; Gabriel Palma Petrielli; Mateus Ferreira Chagas; Isabelle Lobo de Mesquita Sampaio; Liliana Zanelli de Oliveira Martins; Tassia Lopes Junqueira; Edvaldo Rodrigo de Morais; Thayse Aparecida Dourado Hernandes (Nature Communications)
Abstract Alongside the concerns of waste management, plastic production represents a future problem for managing greenhouse gas emissions. Advanced recycling and bio-based production are paramount to face this challenge. The sustainability of bio-based polyethylene (bioPE) depends on the feedstock, avoiding stress on natural resources. This work discusses Brazil’s potential to meet future global bioPE demand by 2050, using sugarcane as feedstock and considering environmental sustainability for production expansion. From the assessed 35.6 Mha, 3.55 Mha would be exempt from trade-offs related to land use change (dLUC), biodiversity, and water availability. The scenario with the highest circularity efficiency would require 22.2 Mha to meet the global demand, which can be accommodated in areas with positive impacts in carbon stocks, neutral impacts in water availability, and medium impacts on biodiversity. Here, we show that dropping demand is essential to avoid trade-offs and help consolidate bioPE as a sustainable alternative for future net-zero strategies.